Biological Asset Accounting Implementation Based on Psak No. 69 - Andayani, Wuryan; T, Sutrisno (Journal of Ecohumanism, 2024)
The purpose of this study is to analyze the implementation of biological assets, productive crops and fair value hierarchies in Agricultural Sector Companies listed on the Indonesia Stock Exchange. The methodology used here is qualitative, including studies on the annual reports of agricultural sector companies in Indonesia. The paper finds that the majority of Agricultural sector companies in Indonesia have implemented PSAK 69 regarding biological assets, PSAK 16 regarding productive crops and PSAK 68 regarding fair value. It can be a guideline for the application of biological assets, productive crops, the application of fair value for other agricultural sector companies. This study used PSAK 69 which was effective as of January 1, 2022 and the content was the same as PSAK 69 which was effective as of January 1, 2018. The implementation of the use of financial standard No. 69 is to produce quality financial reports. Companies make financial reports by referring to accounting standards in order to produce financial reports that can provide reliable, relevant, comparable and comparable information. Thus, the quality of financial reports is getting higher.